Digital branding for nonprofit organizations - Landreth Grau, Stacy (Henry Stewart Talks, 2009)
The impact of the nonprofit sector, Branding and best practices, Key stakeholders, A framework for nonprofit branding, Brand touchpoints, Brand equity